The inversion, formulae for some bessel and hypergeometric transforms (1976)
By an appeal to the Laplace transform and their inverses we have obtained five inversión formulae for some Bessel function transforms. The inversion formula for hyperqeometric transforms have been given whose kernel are the confluent hypergeometric function  1F1(γ - a;  γ; μx) and Gauss hypergeometric function  2F1( a, β, γ;  - 1/ μ x). The results given earlier by Gómez López [8] follow as special cases of our results given in section. 3.